Decomposing financial (in)stability in emerging economies - Etienne Lepers; Antonio Sánchez Serrano (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
The build-up of risks in advanced economies has seen a lot of research efforts in the recent years, while similar research efforts on emerging economies have not been so strong and, when undertaken, have focused mostly on its international dimension. Simultaneously, the financial system of the emerging economies has substantially developed and deepened. In our paper, we construct an index of vulnerabilities in emerging countries, relying solely on data available at international organisations. We group indicators around four poles: valuation and risk appetite, imbalances in the non-financial sector, financial sector vulnerabilities, and global vulnerabilities. On purpose, we depart from early warning models or any other kind of complex econometric constructs. Simplicity and usability are the two key characteristics we have tried to embed into our index of vulnerabilities. We use the results to try to create a narrative of the evolution of vulnerabilities in emerging economies from 2005 to the third quarter of 2015, using innovative data visualisation tools as well as correlations and Granger causalities. We complement our analysis with a comparison between our index of vulnerabilities and the Credit-to-GDP gap.
Keywords: E44; F65; G01; G15; G21; G23; 330; emerging economies; index; financial crises; risk monitoring; credit gap